"Biosynthesis of volatile compounds by hydroperoxide lyase enzymatic activity during virgin olive oil extraction process". (September 2018) - Sánchez-Ortiz, Araceli; Bejaoui, Mohamed Aymen; Quintero-Flores, Angélica; Jiménez, Antonio; Beltrán, Gabriel
Abstract: The approach of this research was to describe the biochemical transformations of minor components of virgin olive oil with high impact on its sensory quality, specifically "volatile compounds" during its extraction process. For this purpose `Picual´, `Arbequina´ and `Hojiblanca´ cultivars were processed at three different harvesting times. Their volatile profiles and levels of enzymatic activity of "hydroperoxide lyase", responsible for the biosynthesis of C6 aldehydes related to "green and fruity notes", were monitored and identified in mesocarp, paste before kneading and paste after kneading based on the catalytic action of crude enzyme extracts. Both of them, volatiles and HPL, were analyzed by incubating with their corresponding substrates and reaction products formed were analyzed by Solid Phase Microextraction-Gas Chromatography and Mass Spectrometry. The results obtained in the present research can be useful in order to develop new markers biochemical whereby improved aroma quality in olive breeding programs or in the design of new protocol of VOO extraction. Graphical abstract: Unlabelled Image Highlights: Biochemical transformations of volatile compounds of VOO are described. The level of enzymatic activity and its relation with final aroma of VOO are analyzed. The results are crucial to improved virgin olive oil sensory quality.